Herpes simplex virus infection of the uterine cervix-relationship with a cervical factor? - Eggert-Kruse, Waltraud; Mildenberger-Sandbrink, Barbara; Schnitzler, Paul; Rohr, Gerhard; Strowitzki, Thomas; Petzoldt, Detlef (Fertility and sterility, 2000)
To determine the prevalence of genital herpes simplex virus (HSV) in women of reproductive age and to evaluate a potential relation of asymptomatic HSV shedding with a cervical factor.
Gesehen am 20.11.2020